Influence of wildfires severity on ash toxicity to early life stages of amphibians - Ferreira, Inês Beatriz da Silva (2021)
Wildfire severity depends on many factors and on their interactions, namely on temperature, geomorphology, fuel characteristics, meteorological conditions, among others. This, in turn, influences the amount of ashes produced during the fire and their chemical composition. Ashes produced by forest fires are a complex matrix composed of organic and inorganic compounds, which are of great environmental concern due to their high toxicity, environmental persistence and tendency to bioaccumulate. Actually, recent studies have confirmed that wildfires act as diffuse source of contamination for the aquatic ecosystems, leading to impairments in their structure and functions. Within the context of contamination driven by wildfire ashes, aquatic early life stages (embryos and tadpoles) of amphibians, due their ecology and vulnerability to environmental disturbances, may be highly susceptible to this type of contamination as they will be exposed to chemical substances released by the ashes the water column and the sediment. This work intended to assess the influence of wildfire severity in pine stands on the ecotoxicity of aqueous extracts of the generated ashes (AEA) on aquatic early life stages of two anuran species: Pelophylax perezi and Xenopus laevis. To attain this goal, embryos of X. laevis and tadpoles of the two species were exposed for 96 hours and 14 days, respectively, to serial concentrations (26.9 to 100 %) of AEA of a medium severity (MS) and a high severity (HS) wildfire. At the end of the exposure periods, the following parameters were evaluated: mortality, malformations, developmental stages, body length (tail-TL, snout-to-vent-SVL and total body-TotL) and body mass (only for tadpoles). Adding to these apical endpoints, effects at the sub-individual level were also monitored for oxidative stress (lipid peroxidation, catalase, total glutathione, glutathione S-transferase-also a xenobiotic transformation enzyme), neurotoxicity (acetylcholinesterase), and energetic metabolism (electron transport system, total lipids, carbohydrate and proteins). Chemical analyses were performed to the two types of ashes and AEA. When comparing MS and HS AEA, the former showed a lower hardness. Furthermore, five (As, Co, Mn, Ni, V) of the ten analysed elements were present at higher concentrations in MS, while only Cd and Pb were at higher concentrations in HS. The assays performed with embryos and tadpoles of the two anuran species, revealed influence of AEA type, species and life stage in the observed ecotoxicological effects. As for lethal toxicity, a similar and significant reduction in survival of embryos of X. laevis and tadpoles of P. perezi was observed at 100 % of MS and HS. Though, tadpoles of X. laevis were more sensitive to MS (survival impaired at concentrations ≥ 26.9 %) than to HS (survival impaired at concentrations ≥ 76.9 %). Regarding sublethal effects, HS was more toxic to embryos of X. laevis than MS, as the former type of AEA significantly reduced TL, SVL and TotL at all tested concentrations, while MS only affected TL. On the contrary, tadpoles of X. laevis were more sensitive to MS; their body lengths and weight were significantly reduced at all tested concentration of MS, though only the two highest concentrations of HS affected these parameters. Tadpoles of P. perezi were more sensitive to HS, having, in general, their body lengths and weight significantly reduced at concentrations ≥ 26.9 % and 59.2 % of MS, respectively. Overall, biochemical markers were not significantly affected by exposure to the two types of AEA. Though it must be emphasized that catalase increase in embryos of X. laevis and tadpoles of P. perezi after exposure to AEA, indicating the occurrence of oxidative stress. This is the first study on the ecotoxicological effects of AEA to amphibians, and showed that the input of wildfire generated ashes, and adsorbed chemicals, may constitute a risk to aquatic life stages of amphibians.